RESEARCH ON COMPREHENSIVE DEVELOPMENT TRENDS OF COLLEGE STUDENTS: A BIBLIOMETRIC ANALYSIS BASED ON CHINA - Liu , Liming; Zainol, Noor Raihani; Samy, Naresh Kumar; Tan , Julia Yin Yin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study employs bibliometric analysis to investigate the trends, hotspots, and future directions in the comprehensive development of Chinese college students from 1995 to 2024. Grounded in UNESCO’s advocacy for education that fosters learners’ comprehensive abilities and China’s focus on cultivating socialist builders with comprehensive development, this research examines 238 articles from CNKI’s core database. With the help of the built-in visualization analysis tool of CNKI，the analysis covers annual publication trends, research topics, disciplinary distribution, influential journals and institutions, and citation frequency. Key findings include phased fluctuations in publication trends, dominance of education-related disciplines, and a strong policy orientation in research topics. The study highlights the need for more interdisciplinary research and practical application in the digital era, providing valuable insights for policymakers, educators, and researchers aiming to enhance higher education strategies in China and even the world.